2014
DOI: 10.1128/aem.01294-14
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Medium pH by Caulobacter crescentus Facilitates Recovery from Uranium-Induced Growth Arrest

Abstract: The oxidized form of uranium [U(VI)] predominates in oxic environments and poses a major threat to ecosystems. Due to its ability to mineralize U(VI), the oligotroph Caulobacter crescentus is an attractive candidate for U(VI) bioremediation. However, the physiological basis for U(VI) tolerance is unclear. Here we demonstrated that U(VI) caused a temporary growth arrest in C. crescentus and three other bacterial species, although the duration of growth arrest was significantly shorter for C. crescentus. During … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…Results revealed that 10 of the 15 mutants exhibited a growth defect in the presence of U relative to growth of the wild type. We later discovered that the pH of PYE medium decreases from 6.5 to 5.7 with addition of 350 M uranyl nitrate, affecting growth phenotypes (25). To uncouple the U response from changes in pH and growth conditions, we tested the ability of each mutant to survive U exposure under buffered conditions (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Results revealed that 10 of the 15 mutants exhibited a growth defect in the presence of U relative to growth of the wild type. We later discovered that the pH of PYE medium decreases from 6.5 to 5.7 with addition of 350 M uranyl nitrate, affecting growth phenotypes (25). To uncouple the U response from changes in pH and growth conditions, we tested the ability of each mutant to survive U exposure under buffered conditions (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Transcriptomic and proteomic studies during U exposure in C. crescentus revealed dozens of genes with significant changes in expression in response to U; these genes do not appear to overlap substantially with those that are variably expressed in response to other heavy metal stresses, such as cadmium (Cd) and chromium, suggesting a divergent cellular response to U(VI) (23,24). This response manifests, in part, as a temporary arrest in cell cycle progression and DNA replication, along with some cell filamentation (a possible consequence of U-induced DNA damage) observed during growth recovery following U detoxification (25). Proteins upregulated in response to U include the periplasmic protein UrcA, a phytase enzyme, two-component signaling factors, and an ABC transporter.…”
mentioning
confidence: 99%
“…C. crescentus is an obligate aerobe with a ubiquitous presence in aqueous environments where it is well‐adapted to life under low‐nutrient conditions (Poindexter, ). Remarkably, Caulobacter species tolerate high concentrations of U (Hu et al ., ; Park and Jiao, ), have been found in U‐contaminated sites (Bollmann et al ., ) and can mineralize U through the formation of uranyl phosphate precipitates (Yung and Jiao, ). Multi‐omics studies to elucidate the U stress response pathways in C. crescentus have revealed that many of the highest induced genes/proteins are, in general, poorly characterized or of unknown function (Hu et al ., ; Yung et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…This build up should eventually obstruct normal cellular function and is noted anecdotally, but lacks concrete evidence. Park and Jiao reported that C. crescentus exhibits growth arrest and cessation of DNA replication when first exposed to uranium [67]. In the same study, they describe a novel mechanism in which C. crescentus raises the pH of the solution making U(VI) less soluble and consequently less toxic [67], which differs from other detoxification strategies which involve reduction and precipitation.…”
Section: Detoxification/resistancementioning
confidence: 93%
“…Park and Jiao reported that C. crescentus exhibits growth arrest and cessation of DNA replication when first exposed to uranium [67]. In the same study, they describe a novel mechanism in which C. crescentus raises the pH of the solution making U(VI) less soluble and consequently less toxic [67], which differs from other detoxification strategies which involve reduction and precipitation. Yung et al studying the same species found in uranium-exposed cells an upregulation of an ABC-type transporter interpreted as possibly providing efflux for detoxification [69].…”
Section: Detoxification/resistancementioning
confidence: 93%